CORRELATION OF LIVESTOCKS PERFORMANCE CHARACTERISTICS TO SELLING PRICE JAWARANDU GOATS IN SAMARINDA CITY EAST KALIMANTAN: KORELASI KARAKTERISTIK PERFORMAN TERNAK TERHADAP HARGA JUAL KAMBING JAWARANDU DI KOTA SAMARINDA KALIMANTAN TIMUR (Jurnal Peternakan Lingkungan Tropis, 2021)
Performance which is assessed as a determinant of the selling price is seen from body measurements. The better the performance condition of the livestock, the higher the price. This research aims to determine the performance characteristics of goats sold and traded at the level of goat breeders and traders, and to determine the performance correlation in determining the selling price of Jawarandu goats in North Samarinda District. This research was conducted from November 2020 to February 2021 in North Samarinda District. The research used a survey method conducted in North Samarinda District. The sampling method at the research location is the total sampling method. Data collection includes performance measurements (shoulder height, chest circumference, body length, horn length, ear length, and body weight calculation). Data were analyzed using multiple linear regression. The results of this study indicate that performance (chest circumference, body length, shoulder height, horn length, ear length, and body weight) has a correlation coefficient value of the selling price of Jawarandu goats in sequence 0.714; 0.635; 0.686; 0.562; 0.458; 0.810. These results indicate that body weight (r = 0.810) has the highest correlation coefficient compared to the performance of other goats because body weight strongly influences the selling price of Jawarandu goats.
Keywords: Array; Array; Array; Array